EVALUASI PEMAHAMAN GURU SMA TERHADAP PEMBELAJARAN FLIPPED CLASSROOM DENGAN PENDEKATAN RASCH - Riskawati; Nur Ifwa Awalya; Nur Aziza; Khaeruddin; Mifta Nurya Anwar; Wahyuni (UIN Sunan Gunung Djati Bandung, 2025)
The advancement of technology has influenced learning activities, including through the Flipped Classroom model, where students study independently at home and class time is used for discussion and collaboration. Teacher understanding and readiness are critical to its success. This study aims to analyze the level of understanding among elementary, junior, and senior high school teachers in South and West Sulawesi regarding the concept, challenges, and classroom implementation of the Flipped Classroom model. A descriptive quantitative method with a survey approach was applied, involving 49 randomly selected teachers. Data were analyzed using the Rasch model to identify the distribution and trends of teacher understanding. The results show that teacher understanding of the Flipped Classroom model is generally high and evenly distributed across demographic groups. These findings provide insight into designing more effective learning strategies across educational levels.